Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Jam Tangan Merek Lorenzo - Mulyani , Sri (CV. ITTC INDONESIA, 2021)
This study aims to: 1) To determine the effect of product quality on purchasing decisions at Mutiara Arloji store in Lubuk Alung market. 2) To determine the effect of price on purchasing decisions at Mutiara Arloji store in Lubuk Alung market. 3) To determine the effect of product quality and price on purchasing decisions at Mutiara Arloji shop in Lubuk Alung market. This research is a descriptive and quantitative research on the purchasing decisions of Lorenzo brand watches at Mutiara Arloji store in Lubuk Alung market. Data were collected using a questionnaire and analyzed using SPSS version 16 for window . The sample in this study were 30 people and determined using Accidental Sampling . Based on the results of the study, it can be concluded: 1) Product quality has a positive effect on purchasing decisions at the Mutiara Arloji store in the Lubuk Alung market. 2) Price has a positive effect on purchasing decisions at the Mutiara Arloji store in the Lubuk Alung market. 3) Product quality and price have a positive effect on purchasing decisions at Mutiara Arloji shop in Lubuk Alung market. With R = 0.750 and Adjusted R Square = 0.562 or 56.20%. With the regression equation Y= 0.616 + 0.335 X1 + 0.537 X2. Suggestions in this study are: 1) Mutiara Arloji Shop to provide Lorenzo brand watches with good durability. 2) Pearl Watch Shops must provide affordable prices in order to compete with the prices of other brands of watches. 3) Pearl Watch Shops must offer Lorenzo brand watches with different variants.